Clinical and Biological Significances of a Methyltransferase-Related Signature in Diffuse Glioma - Zhang, Ying; Liu, Yuqing; Liu, Hanjie; Zhao, Zheng; Wu, Fan; Zeng, Fan (Frontiers in Oncology, 2020)
Methylation of DNA, RNA or protein is a reversible modification. The proteins and genes that regulate this modification can be a candidate target for tumor therapy. However, the characteristics of methyltransferase related genes in glioma remain obscure. In this study, we systematically analyzed the relationship between methyltransferase-related genes expression profiles and outcomes in glioma patients based on The Cancer Genome Atlas and Chinese Glioma Genome Atlas RNA sequencing datasets. Consensus clustering identified two robust groups with significantly different pathological features and prognosis. Then a methyltransferase-related risk signature was built by a Cox proportional hazards model with elastic net penalty. Moreover, the risk score is associated with patients’ clinical and molecular features and can be used as an independent prognostic indicator for patients with glioma. Furthermore, genes associated with the high-risk group were involved in various aspects of the malignant progression of glioma via Gene Ontology analysis and Gene Set Enrichment Analysis. In summary, our study identified a methyltransferase-related risk signature for predicting the prognosis of gliomas.